2019
DOI: 10.1097/sle.0000000000000639
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Double-Tract Reconstruction and Roux-en-Y After Gastrectomy for Gastric Cancer

Abstract: Background: The meta-analysis was performed to compare surgical and functional results of double-tract (DT) and Roux-en-Y (RY) reconstruction, applied in both partial and total gastrectomy. Methods: PubMed, Ovid, Web of Science, Wiley, EBSCO, and the Cochrane Library Central were searched for studies comparing DT and RY after partial or total gastrectomy. Surgical, nutritional, and long-term outcomes were collected and analyzed.Results: A total of 595 patients from 8 studies were included. Operative time, time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In the works of Kim DJ, Kim W et al, and Park et al the data on the lower requirement of vitamin B12 and iron preparations in the postoperative period in those that underwent DT are presented [ [31] , [32] ]. At the same time, other studies have provided data on the absence of a significant difference between changes in blood test parameters (haemoglobin, ferritin, ferritin saturation, total protein, albumin, and cholesterol) and the development of anaemia in those that underwent DT or TG [ 33 ]. For example, although ferritin and haemoglobin levels have been reported to be higher in those that underwent DT, the values of both those that underwent DT or TG were within the normal range.…”
Section: Resultsmentioning
confidence: 99%
“…In the works of Kim DJ, Kim W et al, and Park et al the data on the lower requirement of vitamin B12 and iron preparations in the postoperative period in those that underwent DT are presented [ [31] , [32] ]. At the same time, other studies have provided data on the absence of a significant difference between changes in blood test parameters (haemoglobin, ferritin, ferritin saturation, total protein, albumin, and cholesterol) and the development of anaemia in those that underwent DT or TG [ 33 ]. For example, although ferritin and haemoglobin levels have been reported to be higher in those that underwent DT, the values of both those that underwent DT or TG were within the normal range.…”
Section: Resultsmentioning
confidence: 99%
“…It is still a controversial issue in clinical research, though, whether reconstruction after total gastrectomy for gastric cancer should be done with or without some type of reservoir or placement of the duodenum in the alimentary transit 7 , 17 , 18 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…This technique has proven to be effective in reducing reflux symptoms and mixing bile and pancreatic juice with food, improving digestion and absorption. By allowing passage through the duodenum, it facilitates the investigation and treatment of biliary diseases that require endoscopic intervention, which is quite common in gastrectomized individuals 7 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In some instances, these patients required management with a protein pump inhibitor (PPI) or other medications for symptom relief. Many studies have indicated that proximal gastrectomy with DTR is safe and depending on the case can provide better results when compared to TG [ 5 , [13] , [14] , [15] , [16] , [17] ].…”
Section: Effect On Postoperative Complicationsmentioning
confidence: 99%
“…Double tract means that two pathways have been formed for the passage of food; one for the entry of food into the stomach and duodenum (where most food is expected to flow into) and the other from the esophagus into the jejunum. DTR after proximal gastrectomy consists of three anastomoses: an esophagojejunostomy (EJ-stomy), a gastrojejunostomy (GJ-stomy) and a jejunostomy- jejunostomy (JD-stomy) [ 5 , 6 ]. DTR has been studied as an alternative reconstruction to TG for proximal gastric cancer (PGC) and, for certain patient populations has also become the choice of reconstruction.…”
Section: Introductionmentioning
confidence: 99%